Geteiltes Wissen - Wissensentwicklung in Disziplin und Profession Sozialer Arbeit - Köttig, Michaela; Kubisch, Sonja; Spatscheck, Christian (Theorie, Forschung und Praxis der Sozialen Arbeit, 2023)
As a discipline and profession, social work lives from the constant development of the knowledge shared in and with it. Research, theory formation, teaching and practice form a complex structure in the social context. The volume takes a look at the various relations: Where, by whom and in what way is social work knowledge formed, developed and shared? And what types of knowledge are involved?